Construction and Programming of Bivariate Model for Unsaturated Soil Seepage Calculation - Zhong, Lijia; Liu, Fengyin; Wang, Bo; Zhou, Dong (Frontiers in Earth Science, 2022)
The seepage calculation of unsaturated soil has always been an important subject in the field of geotechnical engineering, and it greatly influences the stability of geotechnical engineering. Currently, most of the unsaturated soil seepage calculation formulas consider only the saturation. In fact, the seepage of the soil is also affected by other factors, such as pore size. Therefore, considering the influence of void ratio in the seepage calculation of unsaturated soil is worthy of further investigation. In this study, a seepage function of unsaturated soil, which considers the influence of dry density and saturation, was constructed and introduced into ABAQUS program. An engineering case was calculated, and the difference between the results considering two variables and that only considering saturation was compared and analyzed. The analysis of the results indicates that this function can better characterize unsaturated seepage, and its subprogram is applicable.